2011
DOI: 10.1007/s11665-010-9751-9
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Obtaining of Nano-Hydroxyapatite Bioactive Films on NiTi Shape Memory Alloy by Electrodeposition Process

Abstract: Nano-hydroxyapatite (n-HA) crystalline films have been developed in this study by electrodeposition method on NiTi shape memory alloy (SMA). The electrodeposition of the n-HA films was carried out using 0.042 mol/L Ca(NO 3 ) 2 AE 4H 2 O + 0.025 mol/L (NH 4 ) AE 2HPO 4 electrolytes by applying a constant potential of 22.0 V for 120 min and keeping the solution temperature at 70°C. The characterization of n-HA films is of special importance since bioactive properties related to n-HA have been directly identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Therefore, the structure and crystallinity of the coating would be significantly affected. For comparative studies, HA crystal electrodeposition was realized on NiTi alloys; more details are shown elsewhere . In a few words, to obtain crystalline HA crystals on NiTi alloys, it was necessary to apply an anodic current of 3.3 A/cm 2 and a thermal treatment at 100 °C for 24 h. The anodization process created a nanometric roughness on the NiTi surface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the structure and crystallinity of the coating would be significantly affected. For comparative studies, HA crystal electrodeposition was realized on NiTi alloys; more details are shown elsewhere . In a few words, to obtain crystalline HA crystals on NiTi alloys, it was necessary to apply an anodic current of 3.3 A/cm 2 and a thermal treatment at 100 °C for 24 h. The anodization process created a nanometric roughness on the NiTi surface.…”
Section: Resultsmentioning
confidence: 99%
“…Figure shows the Raman spectra of HA obtained on the following conditions: (a) as grown on polished NiTi alloy, (b) as grown on anodized NiTi alloy, (c) after heat treatment for 24 h of sample shown in (b), and (d) as grown on the superhydrophilic VACNT films. The sharp band at 961 cm −1 is characteristic of crystalline HA .…”
Section: Resultsmentioning
confidence: 99%
“…Hydroxyapatite (Lobo et al, 2011), zirconia (Qiu et al, 2010), titanium oxide (Qiu et al, 2011), titanium nitride (Jin et al, 2013), and apatite-collagen composite (Sun et al, 2011), are coated on Ti-Ni SMAs to improve the biocompatibility. Among these coating, titanium nitride (TiN), possessing high hardness and good wear resistance, has been used for hip prostheses (Piscanec et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…38,39 In the present work, in addition to investigating the inuence of electrolyte temperature and current density, we have shown that the growth of globular-like nHAp crystals on superhydrophilic-RGO lms is highly inuenced by the nanotopography and wettability properties. The reason for this affirmation is a simple comparison between the same electrodeposition process applied using NiTi alloys 40 and VAMWCNT lms 9 in terms of the temperature and current density. In this comparison, the nHAp crystal growth is only possible on NiTi alloys aer roughening of the surface and thermal treatment.…”
Section: Resultsmentioning
confidence: 97%